PENANAMAN IMAN MELALUI PEMBELAJARAN MATEMATIKA UNTUK KELAS KUTTAB AWAL 3 DI KUTTAB CIMAHI - Elvathna Syafwan (Jurnal TEDC, 2022)
Mathematics is a universal science and is very important in everyday life. In various educational institutions, mathematics is always studied from an early age. Existing mathematics learning generally only prioritizes theoretical understanding. In fact, for school-age children, it is very important to instill the value of faith from an early age. With the hope that a generation of intelligent, faithful and noble Muslims will be born. The purpose of this research, the wider community can get to know more about Sirah Muhammad SAW-based education, known as Kuttab and proven to have given birth to a brilliant generation including Muslim scientists Al Khwarizmi, Al Battani who are experts in the field of mathematics. In Indonesia, Kuttab has been present and spread in several regions. This research method uses a qualitative approach with a descriptive type of research in which research procedures or problem solving are investigated with a description of the subject or object through observations of mathematics learning in class and documentation from the Counting Book used. The results showed that every material in numeracy that was studied was always inserted with Islamic teachings so that students not only understood theory but also embedded faith in their hearts from an early age.